2011
DOI: 10.1002/jbmr.444
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen inhibits Dlk1/FA1 production: A potential mechanism for estrogen effects on bone turnover

Abstract: We have recently identified Dlk1/FA1 (Delta-like 1/FA1) as a novel regulator of bone mass that functions to mediate bone loss, under estrogen deficiency, in mice. In this report, we investigated the effects of estrogen (E)-deficiency and E replacement on serum (s) levels of Dlk1/FA1 (s-Dlk1FA1) and its correlation with bone turnover markers. s-Dlk1/FA1 and bone turnover markers (s-CTx and s-osteocalcin), were measured in two cohorts: a group of pre- and postmenopausal women (n=100) and a group of postmenopausa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
(27 reference statements)
4
17
1
Order By: Relevance
“…In addition, DLK1 favors bone resorption through a nuclear factor-kB-dependent pathway (13). Consistent with these data, serum levels of DLK1 were increased in estrogen-deficient postmenopausal women (15) and inversely correlated with total bone mineral density (BMD) in patients with anorexia nervosa (16) or hypothalamic amenorrhea (17).…”
supporting
confidence: 38%
“…In addition, DLK1 favors bone resorption through a nuclear factor-kB-dependent pathway (13). Consistent with these data, serum levels of DLK1 were increased in estrogen-deficient postmenopausal women (15) and inversely correlated with total bone mineral density (BMD) in patients with anorexia nervosa (16) or hypothalamic amenorrhea (17).…”
supporting
confidence: 38%
“…Delta like 1/FA1 has been established as an inhibitor of adipocyte differentiation and fat mass in vitro and in vivo (Abdallah et al, 2004, 2011b). Thus, we studied the inhibitory effect of FA1 on adipogenic differentiation of myotubes as a consequence of FA1-induced down-regulation of the above indicated adipogenic markers.…”
Section: Resultsmentioning
confidence: 99%
“…Among the multiple physiopathological mechanisms involved in OA, those related to sex hormone control have been attracting much attention, in particular those involving estrogens [27]. The loss of articular cartilage integrity has been shown in several animal models with estrogen deficiency [28,29,30,31,32] and this pattern was supported by a study by Claassen et al [33], who showed that estradiol could suppress the expression of some degradative proteinases in cultured osteoarthritic chondrocytes. Estrogen deficiency plays a relevant pathogenic role in OA, and estrogen deprivation might exert a double effect on normal cartilage: on the one hand, through the direct action of estrogen itself, and, on the other, through the associated increase in subchondral bone turnover [34].…”
Section: Discussionmentioning
confidence: 99%